Analisis Kemampuan Pemahaman Masalah Matematis Siswa pada Materi Barisan dan Deret dengan Pendekatan PMR - Uron Hurit, Roberta; Maran, Meliana Tere; B Teluma, Theresia Lasitania; Petrus Ola, Yoseph; Moron, Anna Nogo (Lembaga Dongan Dosen, 2025)
This study aims to determine the mathematical understanding ability of class XI MIA 2 students of SMA Negeri 1 Titehena on the topic of sequences and series using a realistic mathematical approach. The type of research used is qualitative descriptive research. The subjects of this study were class XI MIA students of SMA Negeri 1 Titehena. The data collection methods used were observation, unstructured interviews and written tests on contextual problems related to sequence and series material. The data analysis techniques used were data reduction, data presentation and drawing conclusions. The results of the study showed that most class XI MIA 2 students of SMAN 1 Titehena already had good mathematical understanding abilities. This can be seen from the students' ability to solve the problems given and work according to the procedure. However, there are some students who do not have a good mathematical understanding related to the steps in solving problems. They emphasize more on the feeling system